MAKNA CATCALLING (Studi Fenomenologi di Desa Masbagik Timur Kecamatan Masbagik Kabupaten Lombok Timur) - Neli Sri Mayana; Solikatun Solikatun; M.Arwan Rosyadi (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2021)
This study aims to know the meaning of catcalling based on the opinion of the perpetrators and the targets and to find out the impact of catcalling on the targets of the action. This study used George Herbert's theory of symbolic interactionism Blumer. This study used a qualitative research method with a phenomenological approach. The techniques of collecting data were participant observation, in-depth interviews, and documentation. Data were analyzed by using reduction data, data presentation (data display), and drawing conclusions or verification. The results showed that catcalling is still found in East Masbagik Village. Catcalling is interpreted by the perpetrators as a joke or a friendly greeting to new people, ways to make friends, and getting attention to increase its existence from the target or their friends. While the meaning of catcalling for the targets is that the perpetrators seek attention from unknown people in public places, disturbance received while in public places, and verbal harassment caused by physical comments and appearances blatantly. Furthermore, the impact of catcalling on the targets refers more to the psychological impact because it causes fear, anxiety, and discomfort for the targets to carry out activities in the location where they got the catcalling